2015
DOI: 10.1016/j.nicl.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in symptom severity and behavior predict neural activation during face processing in adolescents with autism

Abstract: Despite the impressive literature describing atypical neural activation in visuoperceptual face processing regions in autism, almost nothing is known about whether these perturbations extend to more affective regions in the circuitry and whether they bear any relationship to symptom severity or atypical behavior. Using fMRI, we compared face-, object-, and house-related activation in adolescent males with high-functioning autism (HFA) and typically developing (TD) matched controls. HFA adolescents exhibited hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 85 publications
5
27
0
Order By: Relevance
“…A recent study by Scherf and colleagues (2015) demonstrates a relationship for activation patterns of the FG with symptom severity in ASD, while amygdala activation was related to task type. Specifically, more severe symptoms were related to decreased right FG activity while amygdala activation in ASD was much greater in response to scrambled faces compared to TD adolescents.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study by Scherf and colleagues (2015) demonstrates a relationship for activation patterns of the FG with symptom severity in ASD, while amygdala activation was related to task type. Specifically, more severe symptoms were related to decreased right FG activity while amygdala activation in ASD was much greater in response to scrambled faces compared to TD adolescents.…”
Section: Discussionmentioning
confidence: 96%
“…For example, we have recently written about the likelihood that adolescence is a developmental period of vulnerability in autism (Picci & Scherf, ), which is supported by both behavioral and neuroimaging findings (e.g. Scherf, Behrmann, Kimchi & Luna, ; Scherf, Luna, Minshew & Behrmann, ; Scherf et al ., ; Whyte et al ., ). Taking a developmental perspective with this in mind could lead to hypotheses about how neural networks are changing in adolescence.…”
Section: Developmental Lensmentioning
confidence: 99%
“…In addition to the well-established deficits in behavioral and perceptual studies of face processing (Boucher and Lewis, 1992; Harms et al, 2010; Papagiannopoulou et al, 2014), numerous imaging studies have shown reduced activation in the fusiform face area (FFA) in individuals with ASD (Corbett et al, 2009; Hubl et al, 2003; Pierce et al, 2001), indicating changes to the ventral visual stream. Indeed, individual differences in the severity of autistic symptoms have been shown to correlate with activation of the FFA, with greater symptom severity negatively correlated with right FFA activity (Scherf et al, 2015). A robust finding in these studies is a reduction in the amount of repetition suppression seen in response to the repeated presentation of faces, again suggestive of altered activation in visual cortical regions involved in face processing (Ewbank et al, 2014; Fiorentini et al, 2012).…”
Section: Evidence For Alterations In Neural Processing Relevant Tomentioning
confidence: 99%